Comprehensive analysis of glycolytic enzymes as therapeutic targets in the treatment of glioblastoma - Sanzey, Morgane; Rahim, Siti Aminah Abdul; Oudin, Anais; Dirkse, Anne; Kaoma, Tony; Vallar, Laurent; Herold-Mende, Christel; Bjerkvig, Rolf; Golebiewska, Anna; Niclou, Simone P. (PLOS ONE, 2015)
Major efforts have been put in anti-angiogenic treatment for glioblastoma (GBM), an aggressive and highly vascularized brain tumor with dismal prognosis. However clinical outcome with anti-angiogenic agents has been disappointing and tumors quickly develop escape mechanisms. In preclinical GBM models we have recently shown that bevacizumab, a blocking antibody against vascular endothelial growth factor, induces hypoxia in treated tumors, which is accompanied by increased glycolytic activity and tumor invasiveness. Genome-wide transcriptomic analysis of patient derived GBM cells including stem cell lines revealed a strong up-regulation of glycolysis-related genes in response to severe hypoxia. We therefore investigated the importance of glycolytic enzymes in GBM adaptation and survival under hypoxia, both in vitro and in vivo. We found that shRNA-mediated attenuation of glycolytic enzyme expression interfered with GBM growth under normoxic and hypoxic conditions in all cellular models. Using intracranial GBM xenografts we identified seven glycolytic genes whose knockdown led to a dramatic survival benefit in mice. The most drastic effect was observed for PFKP (PFK1, +21.8%) and PDK1 (+20.9%), followed by PGAM1 and ENO1 (+14.5% each), HK2 (+11.8%), ALDOA (+10.9%) and ENO2 (+7.2%). The increase in mouse survival after genetic interference was confirmed using chemical inhibition of PFK1 with clotrimazole. We thus provide a comprehensive analysis on the importance of the glycolytic pathway for GBM growth in vivo and propose PFK1 and PDK1 as the most promising therapeutic targets to address the metabolic escape mechanisms of GBM.